The frequency of non-radiographic axial spondyloarthritis in relation to symptom duration in patients referred because of chronic back pain: results from the Berlin early spondyloarthritis clinic. Issue 12 (21st August 2012) - Poddubnyy, Denis; Brandt, Henning; Vahldiek, Janis; Spiller, Inge; Song, In-Ho; Rudwaleit, Martin; Sieper, Joachim
Abstract : Objective: This study was aimed at investigating the frequencies of non-radiographic axial spondyloarthritis (nr-axSpA) and ankylosing spondylitis (AS) diagnoses and their ratios in relation to symptom duration in patients referred because of chronic back pain and suspicion of axial SpA. Methods: In this monocentre study, orthopaedists and primary care physicians were requested to refer patients with chronic low back pain (duration >3 months) and onset of back pain before 45 years of age to a SpA-specialised rheumatology outpatient clinic for further diagnostic investigation, if proposed screening parameters were present. The ratio of nr-axSpA to AS was analysed in relation to the duration of symptoms. Results: A diagnosis of definite axial SpA was made in 43.7% of the referred patients (n=522). Axial SpA was diagnosed in a similar percentage of about 50% if back pain duration was <9 years but decreased to 36% if symptom duration was >9 years. Nr-axSpA represented the majority of patients (67.3%) only if duration of back pain was 1 year and less at the time of referral. Between 1 and 6 years of back pain duration the probability of nr-axSpA and AS was nearly equal (1–3 years: 52.5% and 47.5%, respectively; 3–6 years: 53.7% and 46.3%, respectively). In patients with back pain duration of 6–9 years, AS was more likely (61.1%) to be diagnosed than nr-axSpA (38.9%), and this increased further over time. Conclusions: Non-radiographic axial SpA represents an important differential diagnosis of back pain, especially in patients with recent symptom onset.